IMAJINASI PERANG DALAM DIGITAL PAINTING - SEPTIMAN GIRSAL, Drs. Syafwan, M.Si, Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this final work is to represent the phenomena and effects of physical warfare to humans through real digital painting.This method of art creation, using five stages of preparation stage, elaboration stage, synthesis stage, realization stage and completion of concepts, and holding digital painting exhibition. In the creation of painting digital artwork writers using hardware and software, in hardware using laptops and pen tablets while in the software the author uses Adobe Photoshop.War is a phenomenon that is very difficult to remove from human life, although people are aware and know that it can cause a lot of harm to all parties, including those who started the war. In this work is a picture of the author's anxiety about the phenomenon of war which resulted in many losses in humans, the resulting loss is very complex both physically and psychologically, the author hopes with this work, can be a reminder of how important it is to maintain peace. In representing the phenomenon of war, the author presents 10 works namely : Immortal, Survival, Sembunyi, Gray, Menunggu, Harapan, Pengungsi, Menyesal, Berurat-berakar and just watching.Keywords: Imajinasi perang, Digital painting, and Surrealist